1997
DOI: 10.1111/j.0022-3646.1997.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of 4‐methyl Sterols From Cultured Dinoflagellate Algal Strains

Abstract: The marine dinojlagellates Prorocentrum micans, Gonyaulax polyedra, Gymnodinium sp., and Alexandrium tamarense, collected from the Adriatic Sea during red-tide blooms, were cultured to investigate the 4-methy l sterol constituents. To ascertain a possible influence of cell age on the 4-methyl sterol content, for one strain (Gymnodinium sp.) we investigated the composition of these constituents at exponential and stationaly growing phases. The lipid material extracted with acetone from the lyophilized algal sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 22 publications
3
49
2
Order By: Relevance
“…CS-295/c. The presence of compound 13 as a dominant sterol appears to be limited mainly to a selection of dinoflagellate genera, including Gymnodinium, Gyrodinium, Heterocapsa, Pfiesteria, Prorocentrum, and Scrippsiella (Harvey et al, 1988;Piretti et al, 1997;Mansour et al, 1999;Leblond & Chapman, 2002. Compound 12 has also been found as a dominant sterol among these genera (Nichols et al, 1984;Mansour et al, 1999;Leblond & Chapman, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…CS-295/c. The presence of compound 13 as a dominant sterol appears to be limited mainly to a selection of dinoflagellate genera, including Gymnodinium, Gyrodinium, Heterocapsa, Pfiesteria, Prorocentrum, and Scrippsiella (Harvey et al, 1988;Piretti et al, 1997;Mansour et al, 1999;Leblond & Chapman, 2002. Compound 12 has also been found as a dominant sterol among these genera (Nichols et al, 1984;Mansour et al, 1999;Leblond & Chapman, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The dominant sterol(s) in diatoms varies depending on the species present, but brassicasterol (24-methylcholesta-5,22-dien-3b-ol), fucosterol (24-methylcholesta-5,24(28)-dien-3b-ol), and b-sitosterol (24-ethylcholesta-5-en-3b-ol) are common lipids of diatoms (Barrett et al 1995;Volkman et al 1998). The compound dinosterol (4a,23,24-trimethyl-5a-cholest-22-en-3b-ol) is found in many dinoflagellate species (Boon et al 1979;Withers 1983;Pirretti et al 1997) and is commonly used as a biomarker for these organisms (Robison et al 1984;Brassell et al 1987;Volkman et al 1998). The other two main algal groups in Lake Malawi, green algae and cyanobacteria, also have specific biomarkers.…”
Section: Methodsmentioning
confidence: 99%
“…The dinoflagellate responsible for red blooms in the Arabian Gulf is Cochlodinium polykrikoides (Richlen et al, 2009, Hamzehei et al, 2013 belonging to the family Gymnodiniaceae, comprising three red tide producing genera -Cochlodinium, Gymnodinium and Gyrodinium. Pirretti et al (1997) reported the presence of dinosterol and dinostanol in Gymnodinium and it is possible that Cochlodinium can also biosynthesize dinosterol and dinostanol and serve as their source in Mesaieed mats. However, neither motile nor cyst stages of these species were found (data not shown).…”
Section: Steroidsmentioning
confidence: 99%